Silver-magnesium fluoride cermet films. 1: Preparation and microstructure. - Gajdardziska-Josifovska, M; McPhedran, R; Cockayne, D; McKenzie, DR; Collins, R (1989)
We have prepared and studied seventeen thin films ranging in composition from pure silver to pure magnesium fluoride. Using mass thicknesses based on quartz crystal oscillators and physical thicknesses obtained from a stylus profilometer, we have measured the void volume fraction of the films as a function of their composition. We have shown the Ag-MgF(2) system to be capable of incorporating a high volume fraction of voids. We report on the results of electron microscope studies of the films, which show the dependence of film microstructure on composition, thickness, and the nature of its substrate.